Review: Musik dan Denyut Jantung Pada Era Digital - Afandi, Ifan Kurnia; Ferdiana, Ridi; Nugroho, Hanung Adi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
Heart rate is one of the vital signs of the body health. In addition, the heart is the main pillar of the body in daily activities. Heart rate measurement can be done anywhere with the number of applications on smartphone, the example on Google PlayStore. Today, Digital Lifestyle can not be separated from the smartphone. This can be seen when the daily activities can not be separated from the smartphone. Today's digital lifestyle can not be separated from the music to support day-today activities. Musik digunakan manusia untuk tujuan yang bermacam-macam. Sebagian orang menggunakan musik untuk berelaksasi dan sebagian lainnya menggunakan musik untuk membangkitkan semangat. This paper presents the relationship between heart rate and the music so it can be used for the development of applications on smartphones. Keywords: Heartbeat; Music; Smartphone